Distribution and Occurrence of Microcrustaceans in Uwanse Stream, Calabar, Cross River State. - Udoh, Ifiok S.; Eyo, Victor Oscar; Etim, Job Bassey (European Academic Research, 2015)
Studies were conducted on the distribution and occurrence of microcrustaceans in Uwanse Stream Calabar, Nigeria between October 2009 and February, 2010. The objectives of this study was to determine the abundance and diversity of microcrustaceans in the Stream. A total of 523 individuals of microcrustaceans belonging to three (3) taxonomic groups (copepoda, cladocera and decapoda) were recorded during the three months sampling period as follows: October 2009, 214 individuals (40.91 %), December 2009, 188 (35.95%) and February 2010, 121 individuals (23.14%). Ecological indices of Microcrustaceans from Uwanse stream showed species were more diverse and richer in a rainy monty (October) than dry season months (December and February). Margalef index (D) was 0.932 (October 2009), 0.955 (December, 2009) and 1.043 (February, 2010). Shanon Wiener (H) was 1.703 (October 2009), 1.688 (December, 2009) and 1.677 (February, 2010). Evenness (E) was 0.915 (October 2009), 0.884 (December, 2009) and 0.891 (February, 2010). Simpson index was 0.805 (October 2009), 0.801 (December, 2009) and 0.789 (J February, 2010). In conclusion, human activities around the stream such as cultivation of vegetables like water leaf, fluted pumpkin, red pepper, tomatoes and scent leaves negatively affected microcrustaceans abundance in the stream during the dry season months as farmers rely solely on water in the stream to grow their vegetables.
Keywords: Microcrustaceans; Distribution; Occurrence; Species Diversity; Uwanse Stream